2018
DOI: 10.2147/tcrm.s147078
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and microorganisms of urinary tract infections in patients with type 2 diabetes mellitus: a retrospective study in China

Abstract: BackgroundUrinary tract infections (UTIs) occur more frequently in diabetic patients. This study was conducted to investigate the prevalence, risk factors and microorganisms of UTIs in Chinese patients with type 2 diabetes (T2D).Patients and methodsA total of 3,652 Chinese inpatients with T2D were reviewed and data on their clinical characteristics, symptoms of UTIs, random blood glucose, HbA1c, glutamic acid decarboxylase antibody, insulin autoantibody, albumin excretion rate in 24-hour urine, urine culture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
34
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
15
34
1
1
Order By: Relevance
“…Analysis of the results showed that the risk of ASB is higher among diabetics especially female than their nondiabetic counterparts, in agreement with previous studies (11,12,19,21,27,28). Among the 220 diabetic patients, 9.55% were positive for bacterial growth which is lesser than studies done in different countries (20,25,27,28), similar to results obtained by Worku et al, in Ethiopia (22) and higher than those reported in China (3.7%) by Ke et al (19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis of the results showed that the risk of ASB is higher among diabetics especially female than their nondiabetic counterparts, in agreement with previous studies (11,12,19,21,27,28). Among the 220 diabetic patients, 9.55% were positive for bacterial growth which is lesser than studies done in different countries (20,25,27,28), similar to results obtained by Worku et al, in Ethiopia (22) and higher than those reported in China (3.7%) by Ke et al (19).…”
Section: Discussionsupporting
confidence: 91%
“…In the previous study in the Saudi diabetic population, Al-Rubeaan et al reported that hypertension and insulin therapy were found to be the significant risk factors for ASB (30). E. coli (41.7%) was the predominant pathogen isolated from urine samples followed by K. pneumoniae (25%) in agreement of different studies in many countries such as China, Nigeria, Bangladesh, Jordan, Sudan and Romania (19,23,24,25,27,28). While Nabaigwa et al in their study in Uganda found that the most uropathogen isolated was S. saprophyticus, followed by E. coli (13).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It should be noted that there is a difference of opinion regarding the effect of diabetes duration and blood sugar control on UTI. The study of vismanthan2009 linked the duration of diabetes to UTI, but not to the study of He2018 (28,36). The relationship between blood sugar control and UTI is also highly controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The association between diabetes, urinary tract infection and gender has been well established [11]. In a 2018 study in China, out of 1,072 women with type 2 diabetes in the study, 341 people were infected and of the 1,783 men with type 2 diabetes in the study, only 68 people had a urinary tract infection (28). In connection with the study of venmans2009, in which the prevalence rate of UTI in men is higher than in women, it is necessary to provide the necessary explanations.…”
Section: Examplementioning
confidence: 96%